Factors Associated with Prolonged Institutionalization in Mentally Ill People with and Without a History of Violence and Legal Involvement: A Cross-Sectional Study - Carvalho de Oliveira, Gustavo (International journal of offender therapy and comparative criminology, 2022)
This is a cross-sectional study carried out on 34 individuals hospitalized for a long period in the Federal District, in Brazil. To evaluate factors related to prolonged institutionalization in mental patients with history of violence and criminal records. Individuals found were assorted into two groups: with and without criminal records. We analyzed 56 items by reviewing medical records and health records. Demographic and social data, history of violence, criminal involvement, medical history, substance use, and other aspects related to long hospitalizations, by reviewing medical and health records. We found a profile of male individuals: single, male, with an average age of 47.6 years, low education, and little professional qualification from correctional facilities or long-term psychiatric clinics and hospitals. Most men had a history of aggressive behavior, a leading psychiatric diagnosis of psychosis, and an issue with polypharmacy. Two factors showed statistical significance and were highly related to longer institutionalizations: polypharmacy and records of hospitalization for violent behavior. Further studies with these populations are needed to increase knowledge on the subject. They can help health care systems to improve and provide broad, humanized and quality assistance with multi-professional teams, aiming to reduce prolonged hospitalizations.